Effect of Temperature, Holding Time, and Addition of Sn on Density on Metal Injection Molding Sintering Process - Ahmad Rendi Maulana; Wardatul Jannah; Danang Yudistiro; Mochamad Asrofi; Mahros Darsin (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Metal injection molding (MIM) is a metal forming technique that combines powder metallurgy with plastic injection molding. MIM is very efficient in manufacturing small and complex products in large quantities. The MIM process has four steps: mixing, debinding, injection molding, and sintering. This research was conducted to determine the effect of variations in Sn addition, temperature, and holding time on the density of Al-PP products after the sintering process. Density is mass per volume so to find out the volume of Al-PP products, the use of a 3D scanner was attempted along with the EinScan application and a mesh mixer. The Taguchi method was used for data processing to determine the influence of variations in Sn addition, temperature, and holding time on density. The calculation of the percentage contribution showed that variations in Sn addition, temperature, and holding time affected density by 47%, 21%, and 3%. Also, 2% Sn addition yielded a reasonably good microstructure formation compared to without Sn addition and 1% Sn addition, where many voids remained in the specimen (the more significant the voids, the lower the density).